Features functional activity kinesthetic and visual sensory systems in athletes of different specializations - Ровний Анатолій Степанович (Anatoliy Rovnyy) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to establish specific effects of different sports on functional status and co mood kinesthetic and visual analyzers skilled athletes. Materials and Methods: the study was conducted on athletes qualified five sports: modern pentathlon, volleyball, basketball, handball and fencing. We used methods of difference sensometry and mathematical statistics. Results revealed that the sensitivity of sensor systems depend on the specifics of sports activities and sports equipment. Conclusions: the complex is set internally sensor and between sensory bonds that are formed on the basis of the specific sports activity